2012
DOI: 10.1097/fjc.0b013e31823a0f31
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Purinergic Neurotransmission in Isolated Atria of Streptozotocin-induced Diabetic Rats

Abstract: Cardiac dysfunctions are described in diabetes. However, the role of purinergic neurotransmission in diabetes-related cardiovascular diseases is unknown. The purpose of this study was to evaluate the purinergic neurotransmission in isolated atria from streptozotocin-induced diabetic rats. The animals were grouped as control and diabetic with 30 days (D30) and 60 days (D60) after streptozotocin-induced diabetes. The isolated left and right atria were used in functional experiments. The effects of adenosine trip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…This decreased purinergic response correlates well with a decreased similar response recently found in heart atria of STZ-treated rats. 5 As for the TR, we also found an apparent discrepancy between the vas deferens tonic contractions elicited by endogenous NA, which only elicited a mild increase in D60 (Figure 2(d)), and the drastic increase elicited by exogenous NA (Figure 3). Our data are only in partial agreement with the earlier observation of an increase of the purinergic and noradrenergic components of electrically induced vas deferens contractions of diabetic rats.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…This decreased purinergic response correlates well with a decreased similar response recently found in heart atria of STZ-treated rats. 5 As for the TR, we also found an apparent discrepancy between the vas deferens tonic contractions elicited by endogenous NA, which only elicited a mild increase in D60 (Figure 2(d)), and the drastic increase elicited by exogenous NA (Figure 3). Our data are only in partial agreement with the earlier observation of an increase of the purinergic and noradrenergic components of electrically induced vas deferens contractions of diabetic rats.…”
Section: Discussionmentioning
confidence: 59%
“…3 There are several theories that describe mechanisms related to the development of hypertension in diabetics. 1,4,5 For example, diabetic rats have a decrease in the levels of nitric oxide (NO) produced by acetylcholine in vascular endothelium and a higher incidence of oxidative stress in coronary arteries. 4 Common factors to diabetes and hypertension are oxidative stress and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum response of [Ca 2+ ] i to exogenous ATP was increased in diabetic cardiomyocytes [798]. Modulation of purinergic neurotransmission via P2YR in isolated atria of STZ-induced diabetic rats has been reported [799].…”
Section: Diabetic Cardiomyopathymentioning
confidence: 95%
“…Aberrant neurotransmission seems to be a key feature of arrhythmogenicity and a recently published study showed alterations in purinergic neurotransmission in the atria of diabetic rats [104]. AF may also be provoked in individuals with PAF and normal autonomic function by isoprenaline implying an increased susceptibility despite normal cardiovascular reflexes [105].…”
Section: Autonomic Dysfunction and The Atrial Substratementioning
confidence: 99%